Beyond planning and liberalization: Foreign trade and industrial development in Turkey - Babacan, Mehmet (Palgrave Macmillan, 2018)
After a brief open-economy experience during the 1920s, the Turkish economy could be regarded as state-controlled, planned, and partially closed for the following half a century. Trade, meanwhile, played a limited role and, aside from imported raw materials and exports of agricultural products, did not constitute a significant portion of economic activity. Industry developed-though limited-under a strategy of import substitution in 1960s and 1970s. Along with other major developing countries, Turkey has also witnessed a period of commercial and financial openness, export-oriented industrial production, and a growth model that led to high growth rates, increasing indebtedness at the state level, and budget and current account deficits in the 1980s. Political and macroeconomic instability for the whole 1990s led to unsteady growth cycles under unfinished industrialization and unregulated liberalization processes. The AK Party period (2002-2017) represents a threshold for Turkish industrial, commercial, and financial expansion within a relatively stable environment that then faced several challenges. The first decade of the AK Party government is often described as the final attempt to do the unfinished job of liberalization, both political and economic. Between 2012 and 2017 however, Turkey’s industry, businesses at all scales, financial, and political institutions have been subjected to difficult stress tests, revealing unresolved structural issues. New challenges due to the changing nature of world politics, regional and internal dynamics, and global economic developments, however, are now forcing Turkey to revisit its export-led growth strategy based on reindustrialization, producing more capital-intensive goods with a greater technology component. This chapter asserts that Turkey’s rising trade around the world could hold strong potential with respect to reindustrialization in strategic sectors. Lastly, a new phase of trade expansion should be launched over not only employment but also the development of a high-skilled labor force, proprietary technology in strategic sectors, and sustainable finance.
Keywords: Deindustrialization; Economic Development; Industrial Policy; O10; O14; O21; O24; O25; O52; Planning; Reindustrialization; Trade Policy; Turkey